Diagnosing students difficulties in solving mathematics test the TIMSS model at the number domain - Munaji, Munaji; Mutadi, Mutadi (AIP conference proceedings, 2023)
This research is aimed to diagnose students’ difficulties in completing the TIMSS model mathematics test on the domain number content. This research is included in quantitative descriptive research. The subjects of this study involved eighth-grade students of junior high school in the city of Cirebon. Data collection was carried out in August – September 2020 with a sampling technique using a simple random sampling technique of 676 students from 12 public and private schools. The research instrument is the TIMSS model of mathematics test in the form of multiple-choice and short answers as many as 14 items which are translated into Indonesian in the number content domain. Data analysis was using the package generalized the deterministic inputs, noisy and gate (GDINA) on cognitive diagnostic model (CDM). The data analyzed from the Q-Matrix which contains the attributes that must be mastered by students and student responses which are a description of the students’ abilities actually, produce possible latent attribute output from the Q-Matrix which is then used to see which parts of the attributes students experience. Difficulty with the most dominant difficulty percentage. The results showed that students experienced difficulties which were indicated by not being able to understand the commutative nature of integer arithmetic operations, unable to estimate the result of the nearest decimal number from a fractional number, with each of these attributes included in the knowing domain. Students’ difficulties can also be seen from the results of the analysis which show that students cannot combine information from two different sources to solve problems with multiple steps, with cognitive reasoning domain and number sequence problem, with cognitive domain applying. The results of the analysis also show that students have difficulty in finding number patterns with cognitive domain reasoning.